Analisis Pendapatan Usahatani Padi Sawah Di Desa Tonom Kecamatan Dumoga Timur Kabupaten Bolaang Mongondow - Christian Richard Wales Wales; Mex F. L. Sondakh; Gene H. M. Kapantow (Sam Ratulangi University, 2022)
The purpose of this study is to analyze the income of lowland rice farming in Tonom Village, Dumoga Timur District, Bolaang Mongondow Regency. This research was conducted for 3 months, from November 2021 to January 2022. The data used in this study were primary data and secondary data. The sample was selected using a proportional stratified random sampling method (Proportionate Stratified Random Sampling). The population was divided into three strata based on the area of land planted with lowland rice, namely strata I (land area 1 Ha), Strata II (land area 1-2 Ha) and strata III (land area 2 Ha). The number of samples is 30 people from 116 farmer population. The results of this study indicate that the income of lowland rice farming per hectare at strata I, II, and III respectively is Rp. 6,029,865, Rp. 6,241,915, and Rp. 6,257,939. This shows a tendency that the larger the cultivated land, the higher the income per hectare from lowland rice farming.